La pedofilia tra psichiatria e diritto - Vari, Autori (Il sogno della farfalla, 2010)
The text reproposes the minutes of the meeting held on 7th May 2010 at the University of Chieti, which saw the participation of the psychiatrist Andrea Masini, the criminal lawyer Clementina Ruggieri, the deputy prosecutor of the Republic of Rome Francesco Dall’Olio and the journalist Federico Tulli (all of whom took part in the opening addresses), as well as numerous other psychiatrists and psychologist. The meeting, organised before the recent wave of news concerning cases of paedophilia at the heart of the Catholic Church, studied in depth the nature of paedophilia, its cultural and historical roots, its psychiatric and legal framework, as well as the perspectives of treatment of victims of sexual abuse. An underlying factor throughout the entire meeting was the refusal of a definition which considers paedophilia a form of sexuality.